Authorship and Ownership of AI-Generated Works in Indonesia: A Doctrinal and Comparative Review - Praja, Chrisna Bagus Edhita; Riswandi, Budi Agus; Wartini, Sri; Hakim, Hary Abdul; Espares, Gerald Antang (Jurnal Media Hukum, 2000)
The rise of generative artificial intelligence (AI) challenges the doctrinal foundations of copyright law in Indonesia, particularly the human-centered definition of authorship under Law No. 28 of 2014. This article examines whether Indonesia’s copyright regime can accommodate AI-generated works within its current legal framework and whether adapting the concept of Work Made for Hire (WMFH) can provide a solution to growing legal uncertainties. Using a doctrinal and comparative method, this study analyzes the limits of Indonesian copyright provisions, especially Articles 1(2), 34, and 36, and compares them with legal approaches from the United States, the United Kingdom, and India. While U.S. law requires human authorship for protection, the UK and India allow copyright to be granted to the person who organizes or directs the creation of the work, even if produced by AI. Based on natural rights, incentives, and utilitarian theories, this article proposes a legal reform in Indonesia that would allow copyright ownership to be granted to the human who initiates or controls the AI system. This approach balances legal certainty with the need to support innovation, while preserving the human focus of copyright law.